Normal variations in rate of albumin excretion and albumin to creatinine ratios in overnight and daytime urine collections in non-diabetic children. Issue 6497 (14th September 1985) - Rowe, D J; Bagga, H; Betts, P B
Abstract : Urine albumin excretion measured over consecutive weekends and on repeated first morning collections from normal children showed considerable variation both during the day and from day to day in each subject. The results emphasise the need for repeated measurement of albumin excretion in children to confirm the presence of persistent microalbuminuria.